Emission-angle-dependent colour properties of full-colour quantum-dot light-emitting diode displays - Jeong-Wan Jo; Yoonwoo Kim; Sung-Min Jung; Jong Min Kim (Results in Physics, 2025)
Electroluminescence quantum dot light-emitting diodes (QD-LEDs) have attracted significant attention as self-emissive pixel devices for next-generation displays, owing to their wide colour selectivity and high colour purity. In this study, we developed a computational framework to analyse the optical characteristics of the QD-LEDs using an optical transfer matrix method, which describes light propagation across the multiple optical layers of the devices. We investigated the optical properties of a typical bottom-emission QD-LED device architecture. The angular radiances for red, green, and blue emission of QD-LED devices were fully calculated by a grid search method for hundreds of thickness combinations of transport layers and an anode electrode, to maximise the brightness in the normal direction while minimising angular colour shift. The brightness and the angular colour properties of the display pixel, where red, green, and blue QD-LED devices are integrated under the same thickness configuration, are highly sensitive to the layer thickness combination. Through the computational framework, we achieved a hypothetical full-colour QD-LED display pixel having a colour shift of less than 0.025 and stable correlated colour temperature between 5,600 K and 7,000 K as the outcoupling angle increased from 0° to 80°. We believe that the computational framework designed in this study is useful for designing and optimising the optical configuration of the QD-LED device architecture for the next-generation high-image-quality full-colour AM displays based on QD-LED technology.